Computation of seismic translational and rotational displacements of cantilever retaining wall with shear key. Issue 130 (March 2020) - Jadhav, Prajakta R.; Prashant, Amit
Abstract: This study proposes a displacement based design methodology for cantilever retaining walls with shear key to enhance its performance under seismic loading. Two-dimensional, plane strain finite element dynamic analyses of cantilever retaining wall with different locations of shear key have been performed in OpenSees, which is validated through case studies. Deformation modes and failure mechanism are studied in detail and the model with shear key at heel is proposed as the suitable configuration. The existing double wedge model has been updated to analytically compute seismic sliding displacements of cantilever retaining wall with shear key. A total of 64 cases of analysis have been performed by varying height and toe–widths of wall and subjecting it to four different earthquakes, each scaled to 0.12 g, 0.24 g, 0.36 g and 0.6 g. Suitable design factors have been proposed to estimate peak rotational displacements, residual rotational displacements and peak sliding displacements by comparing the results from FEM analysis and double wedge model. Highlights: Method is proposed to compute seismic displacements of retaining wall with shear key. Wall with shear key below heel underwent lesser seismic displacements. Horizontal slip plane from base of shear key is suggested for stability analysis. The proposed method suggests modified double wedge model to compute sliding displacements Displacement factors are proposed to estimate seismic rotations in wall with shear key.